International Cost Differences: A Comparison of Canadian and United States Manufacturing Industries - Oksanen, Ernest H.; Williams, James R. (The Review of Economics and Statistics, 1978)
Ernest H. Oksanen, James R. Williams, International Cost Differences: A Comparison of Canadian and United States Manufacturing Industries, The Review of Economics and Statistics, Vol. 60, No. 1 (Feb., 1978), pp. 96-101